2014
DOI: 10.1093/carcin/bgu102
|View full text |Cite
|
Sign up to set email alerts
|

Paxillin promotes tumor progression and predicts survival and relapse in oral cavity squamous cell carcinoma by microRNA-218 targeting

Abstract: High-risk human papillomavirus (HPV) 16-infected oral cavity squamous cell carcinoma (OCSCC) differs significantly from non-HPV-infected OCSCC. However, the molecular pathogenesis of HPV-infected OCSCC remains unclear. Paxillin (PXN) has been reported to promote lung tumor progression by miR-218 targeting. In addition, expression of miR-218 has been shown to be reduced by HPV16 E6 in cervical cancer. We thus asked whether PXN can promote tumor progression by E6-reduced miR-218 in OCSCC, especially in HPV-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…Chemically-induced pro-tumoral factors, drugs and environmental milieu (25), represent another domain that could explain HPV + -triggering conditions. Last but not least, the omics domain (26) may bring additional data into this field, as there are data showing a pro-tumoral association of HPV + lesions with miRNA profiles and/or particular proteomics patterns (27). …”
Section: Discussionmentioning
confidence: 99%
“…Chemically-induced pro-tumoral factors, drugs and environmental milieu (25), represent another domain that could explain HPV + -triggering conditions. Last but not least, the omics domain (26) may bring additional data into this field, as there are data showing a pro-tumoral association of HPV + lesions with miRNA profiles and/or particular proteomics patterns (27). …”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have reported that paxillin may be implicated into the pathogenesis of diverse human malignancies. For example, German et al24 showed that paxillin could promote tumor angiogenesis by regulating the expression of neuropilin 2; Mackinnon et al25 found the overexpression of paxillin in premalignant areas of hyperplasia, squamous metaplasia and goblet cell metaplasia, as well as dysplastic lesions and carcinoma in high-risk patients; Wu et al26,27 further reported that paxillin upregulation induced by miR-218 suppression might be an independent predictor of survival and relapse in nonsmall cell lung cancer and oral cavity squamous cell carcinoma; Xiao et al28 reported that paxillin was strongly expressed in gastric adenoma compared with that in nonneoplastic mucosa and carcinoma, and also found that the aberrant expression of paxillin might be implicated into the differentiation, growth and metastasis of gastric carcinoma and Sen et al29 indicated that paxillin regulated prostate cancer proliferation by serving as a mediator between extranuclear kinase signaling and intranuclear transcriptional signals. Consistent with these previous findings, our data revealed the overexpression of paxillin mRNA and protein in human glioma tissues compared to that in normal brain tissues and found an increasing tendency of paxillin expression from grade I to grade IV.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have investigated the underlying mechanisms of paxillin in carcinogenesis and cancer progression of various malignancies 24,26,27,29. However, the mechanism of action on how paxillin expression impacts human gliomas remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Paxillin [48][49][50] and JNK [51,52] are currently two of the well known focal adhesion signaling components involved in tumor progression. Previously, the positive effect of JNK on regulating paxillin phosphorylation for tumor progression has been demonstrated [28], and inhibition of the JNK activity significantly reduced the migration rates of HCC cells via attenuation of paxillin phosphorylation at Ser178 [53].…”
Section: Discussionmentioning
confidence: 99%